PEMBELAJARAN WAWANCARA BAHASA JAWA RAGAM KRAMA (STUDI KASUS SISWA KELAS VIII I DI SMP N 1 KARAS KABUPATEN MAGETAN TAHUN PELAJARAN 2016/2017) - Indriawati, Susiani; Rohmadi, Muhammad; Wijayanti, Kenfitria Diah (Universitas Sebelas Maret, 2018)
This research aims at describe learning interview of speech level krama javanese language of VIII I students in SMP N 1 Karas which include: (1) the teacher perception of learning interview speech levels of krama; (2) the planning of learning interview speech levels of krama; (3) the implementation of learning interview speech levels of krama; (4) the obstacles in learning interview speech levels of krama; (5) the effort to solve learning interview speech levels of kramas’ obstacle. This research is qualitative research which took sample in SMP N 1 Karas Magetan. The sample technique used is purposive sampling technique. The data collecting technique was conducted through observation, informants, and documents. Data analysis used in this research is descriptive analysis.The researches result showed that: (1) the perception of Javanese language teacher SMP N 1 Karas Magetan about learning interview speech levels of krama is important for student and student must practice more, government regulation is needed to maximize the purpose of study; (2) the planning of learning interview speech levels of krama VIII I class SMP N 1 Karas Magetan using syllabus and RPP made by MGMP and adjusted to school condition; (3) the implementation of learning interview speech levels of krama VIII I class SMP N 1 Karas Magetan done by the teacher using demonstration, question and answer, and guided discussion method; (4) the obstacles faced in learning interview speech levels of krama VIII I SMP N 1 Karas Magetan are: (a) limited time for studying the subject; (b) lack of students’ skills using Javanese language krama variety; (c) the students are less actively asking at the time of learning; (d) the students got difficulties copying the text into description form; (5) the ways to overcome these problems: the teacher maximize time allocation; (b) the teacher pushing the students to use and familiarizing themselves with krama language; (c) the teacher gives the students motivation to be active in the class; (d) the teacher guide students when they arrange a list of interview questions.